Maintenance Olaparib in Patients With Newly Diagnosed Advanced Ovarian Cancer. Issue 2 (February 2019) - Moore, Kathleen; Colombo, Nicoletta; Scambia, Giovanni; Kim, Byoung-Gie; Oaknin, Ana; Friedlander, Michael; Lisyanskaya, Alla; Floquet, Anne; Leary, Alexandra; Sonke, Gabe S.; Gourley, Charlie; Banerjee, Susana; et al.
Abstract : (Abstracted from N Engl J Med 2018;379:2495–2505) Standard-of-care therapy for patients newly diagnosed with advanced ovarian cancer consists of frontline cytoreductive surgery and adjuvant platinum chemotherapy. Approximately 70% of these patients have a relapse within 3 years.